Experimental Statistical Analysis of Tensile and Shear Properties of the Jute Fabric Epoxy Composites - Kumar Maharshi; Shivdayal Patel (Journal of Natural Fibers, 2022)
The main objective of this study was to determine the mechanical properties and their analysis using uncertainty analysis of biodegradable Jute fabric composite. Jute fabric composite samples were fabricated using Vacuum infusion method (VIM) and mechanical tests such as tensile and shear tests were performed. Fiber volume fraction of 38% was achieved after fabrication and samples for tensile and shear tests were cut as per ASTM standards. A novel approach for making the notch on the shear samples was developed using the Vertical grinding machine (VGM) where better control over the notch dimensions was achieved. The use of Abrasive water jet machining (AWJM) for cutting of samples was preferred over conventional Hand Grinder (HG) due to higher accuracy on the dimensions and better stress results. The samples which were cut using AWJM showed the 52.3, 62.4, and 15.4% higher shear stress, modulus and strain, respectively, than those cut using HG. Both tensile and shear tests showed non-linear behavior and variability in the results which had little influence over the reliability of its mechanical properties. These characteristics were then confirmed through scanning electron microscope (SEM) images where fiber breakage, resin pockets, matrix cracking, and permeation of the matrix in the fabric were observed. The uncertainty analysis of these test results using different distribution parameters helped to understand the key parameters for product design using such material and optimize the factor of safety, which is an important consideration when using the composite material. The significance and reliability of such composites could help replace the E-glass fiber composite for aerospace and automotive applications.